Bilirubin binding in jaundiced newborns: from bench to bedside? - Ahlfors, Charles E.; Bhutani, Vinod K.; Wong, Ronald J.; Stevenson, David K. (Pediatric research, 2018)
Background: Bilirubin-induced neurologic dysfunction (BIND) is a spectrum of preventable neurological sequelae in jaundiced newborns. Current total plasma bilirubin ( B T ) concentration thresholds for phototherapy and/or exchange transfusion poorly predict BIND. Methods: The unbound (free) bilirubin ( B f ) measured at these B T thresholds provides additional information about the risk for BIND. B f can be readily adapted to clinical use by determining B f population parameters at current B T thresholds. These parameters can be established using a plasma bilirubin binding panel (BBP) consisting of B T , B f , and two empiric constants, the maximum B T ( B Tmax ) and the corresponding equilibrium association bilirubin constant (K). Results: B Tmax and K provide the variables needed to accurately estimate B f at B T < B Tmax to obtain B f at threshold B T in patient samples. Once B f population parameters are known, the BBP in a newborn can be used to identify poor bilirubin binding (higher B f at the threshold B T compared with the population) and increased risk of BIND. Conclusion: The BBP can also be used in jaundice screening to better identify the actual B T at which intervention would be prudent. The BBP is used with current B T thresholds to better identify the risk of BIND and whether and when to intervene.